Endometrial mucosa histopathology and hormonal receptors in postmenopausal women receiving hormone therapy - Valer, Victoria (2005)
Abstract Objectives: To determine correlation between hormone therapy and endometrial mucosa estrogen, progesterone receptors and endometrial histological pathology in postmenopausal women. Material and Methods: Forty postmenopausal women between 43 and 60 years old with climacteric syndrome received oral continuous 2 mg of 17 beta estradiol and 1 mg of noresthisterone acetate. Basal and 8 months post treatment edo metrial biopsies were processed for histopathologic and immune histochemical studies for estrogen and progesterone receptors. Results: Physiologic menopause occurred between 42 and 52 years old, average 46,4 years. Main climacteric symptoms on first consultation were arthralgia 90%, emotional lability 82,5%, dysparenta 75%, hot flashes 27,5% and relative urine incontinence 17,5%. Post treatment emotional lability was 7,5% arthralgia 5%, relative urine incontinence 5%, hot flashes 2,5%, paresthesia 2,5%, and cephalea 2,5%. The histopathologic study of basal endometrial mucosa showed simple hyperplasia in 10% and atrophy in 90%; atrophy was present in every case following treatment. Basal receptors expressed in the endometrial mucosa were ER (+) 12,5%, PR (++) 12,5%, and post-treatment ER(+) 2,5%, ER (+++) 2,5%, and PR (+) 2,5%. Conclusions: Oral daily combined therapy consisting in 2 mg of beta estradiol and 1 mg of norethisterone produced endometrial atrophy in patients with previous hyperplasia and statistical significant drop in the expression of estrogen and progesterone receptors between the basal sample and the 8th month sample.